Liquid hydrogen and synthetic sustainable aviation fuel: A European airline case study - Stuart, Charles; Spence, Stephen (My University, 2025)
There is much debate surrounding Liquid Hydrogen (LH2) and Sustainable Aviation Fuel (SAF) across the aviation industry in terms of future fuel applications for decarbonisation. This study aims to quantify the real-world energy performance of LH2 and SAF powered aircraft in order to determine the optimum energy carrier for short-haul operations. An operational case study was performed comparing the energy performance of LH2 and SAF-powered aircraft, through simulation of each configuration over a day of airline flights to and from Ireland using a novel real-world operations simulation framework. Aircraft models were developed for the B737-800NG and B737-8200 aircraft using physics-based and semi-empirical methods, which were validated, and subsequently calibrated against a broad range of real-world flight data, yielding average total fuel burn errors of 1.6% against test data for both aircraft models. Three equivalent LH2-powered aircraft models were designed with varying LH2 tank gravimetric indices, along with an intercooled-recuperated LH2 configuration. Each aircraft was simulated over a full day of operations, where the fleet-wide well-to-wake energy consumption and cost was compared for each LH2 aircraft and three SAF candidates – one power-to-liquid pathway using carbon obtained from direct air capture, and two ASTM-approved SAF pathways using biogenic carbon feedstocks with alcohol-to-jet and Fischer Tropsch processes. Despite higher in-flight energy consumption, the LH2 aircraft yielded lower well-to-wake energy consumption in almost all cases, where the direct air capture method for SAF was found to be at least 44% more energy intensive than LH2, which may be a deterrent for future fuel applications despite challenges with LH2 infrastructure and aircraft design. Low-carbon ASTM-approved SAF pathways using biogenic feedstocks yielded maximum energy penalties between 14–27% compared to the LH2 configurations. The inter-cooled-recuperated LH2 engine resulted in a fleet-wide energy reduction of 4.4%, increasing the viability of LH2 aircraft against SAF-powered aircraft.
PUBLISHED
Keywords: Smart & Sustainable Planet